(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an in-depth analytical study of the structure and long-term dynamics of loans extended by service-oriented commercial banks to manufacturing enterprises.